A Primer on Macroeconomics - Beveridge, Thomas (Business Expert Press, 2013)
Ebook from IG Library ; Economics, far from being the 'dismal science,' offers us valuable lessons that can be applied to our everyday experiences. At its heart, economics is the science of choice and a study of economic principles that allows us to achieve a more informed understanding of how we make our choices, whether these choices occur in our everyday life, in our work environment, or at the national or international level. This book represents a common sense approach to basic macroeconomics, and begins by explaining key economic principles and defining important terms used in macroeconomic discussion. It uses a single unifying tool--aggregate demand and aggregate supply analysis--to probe differing perspectives on macroeconomic policies. If you're a student, and perhaps a student in business school settings, this book will deliver clear statements of essential economic principles, supported by easy-to-understand examples, and uncluttered by extraneous material; the goal being to provide a concise readable primer that covers the substance of macroeconomic theory.